1997
DOI: 10.1161/01.res.81.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Transient Outward Current in Mouse Ventricle

Abstract: Developmental changes in the transient outward K+ current (Ito) in mouse ventricular myocytes were assessed by the whole-cell patch-clamp technique. The density of Ito in mouse ventricular myocytes was significantly increased from the day-1 neonate to the adult. At +50 mV, the density of Ito was 3 +/- 1 pA/pF in the day-1 neonate, 15 +/- 3 pA/pF in the day-14 neonate, and 19 +/- 4 pA/pF in the adult (P < .01). Unlike other species, the rate of Ito inactivation significantly slowed in mouse ventricular cells du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
87
0
3

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 14 publications
21
87
0
3
Order By: Relevance
“…Age-dependent differences in the action potential shape have been shown in isolated cells from several species (12)(13)(14)(15)(16), including human atria (4,5). In mouse ventricle (15,16) and rat ventricle (13,14), the neonatal action potential has a slower early repolarization phase and more pronounced early plateau.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-dependent differences in the action potential shape have been shown in isolated cells from several species (12)(13)(14)(15)(16), including human atria (4,5). In mouse ventricle (15,16) and rat ventricle (13,14), the neonatal action potential has a slower early repolarization phase and more pronounced early plateau.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse ventricle (15,16) and rat ventricle (13,14), the neonatal action potential has a slower early repolarization phase and more pronounced early plateau. Similar age-dependent differences have been demonstrated in the human atria from intact atrial strips (5) The effects of changes in the action potential waveform on the amplitude of I Ca and the Ca 2ϩ transient have been most clearly shown by using the technique of applying recorded action potentials as voltage waveforms to which the cell is "voltage clamped."…”
Section: Discussionmentioning
confidence: 99%
“…In a variety of species, including the mouse, neonatal cells are significantly smaller than adult myocytes (21,42,49). We assumed that the neonatal cell was a cylinder 50 m in length and 9 m in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…Wang and Duff (49) showed that transient outward current (I to) density increases greatly during development in the mouse, suggesting that these currents play a smaller role in repolarization in neonatal hearts than in adult hearts. I to was also shown to inactivate faster, and with simpler kinetics, in day 1 neonatal compared with adult cells.…”
Section: Methodsmentioning
confidence: 99%
“…Other investigators also found that the DM-related suppression of I to explains the prolongation of APD in diabetic laboratory rat ventricular muscle [21] and ventricular myocytes from diabetic laboratory rats [32]. Recently, Wang and Duff [33] examined developmental changes in the I to in mouse ventricular myocytes by whole-cell patch-clamp techniques, and concluded that the developmental increase in the density of I to contributes to the age-related shortening of APD in mouse ventricle. Based on this finding, we can speculate that the diabetic state may lead to a lack of development of ionic channels responsible for I to and/or a decrease in the density of the channels, compared to the non-diabetic state.…”
Section: Discussionmentioning
confidence: 97%